“THE IMPORTANCE OF MUSEUMS IN THE CONTEMPORARY WORLD” - Khamidova Shakhnoza Ravshanovna (INTERNATIONAL JOURNAL OF SCIENCE-INNOVATIVE RESEARCH, 2025)
Museums have long been regarded as vital institutions for the preservation of cultural heritage, education, and collective memory. In the modern era, their significance has expanded beyond traditional functions. Today, museums serve as dynamic centers of learning, dialogue, and intercultural communication. They integrate innovative technologies, provide inclusive platforms for diverse communities, and contribute to both cultural diplomacy and sustainable development. This article explores the role of museums in contemporary society, analyzing their educational, social, and economic impact, while also addressing challenges they face in the digital age.